Reaching a rare diagnosis of delusional parasitosis (Bangladesh Journal of Psychiatry, 2021)
Delusional parasitosis have been found to be a rarely diagnosed disorder. It may be underestimated in the psychiatric assessment, as well, in literatures because patients with delusional infestation do not believe that their symptoms are delusional and are reluctant to see a psychiatrist. Nevertheless, delusional infestation can be distinguished from other psychiatric disorders if given proper attention in history, assessment and evaluation to rule out other mimics. Our aim in this article was to describe and establish a case of delusional parasitosis presented to our NIMH inpatient.Bang J Psychiatry 2021;35(1): 15-16